Some milestones of the philosophical essay in 2010 (XXI Century. Spanish Literature and Culture, 2012)
This work analyzes the Spanish essay’s most important contributions of 2010. The thematic variety of the essay is evident. The essays achieved provide a balance between high-minded thought and lighthearted entertainment. The article pays special attention to the most important philosophical essays.
Keywords: essay; philosophy; thought; Spanish essay 2010